Satisfaction With Primary Care Among the Foreign-Born and the General Population in Finland: A Survey-Based study - Valentina Kieseppä PhD; Regina García Velázquez PhD; Tuulikki Vehko PhD; Anu Castaneda PhD; Hannamaria Kuusio PhD (SAGE Publishing, 2024)
Foreign-born people have been found to be less satisfied with health care than native populations across countries. However, studies on differences in satisfaction with treatment between different foreign-born groups are lacking. This study explores differences in satisfaction with primary health care between the foreign-born population from different regions of origins and the general population of Finland. The study uses survey data on foreign-born population (n = 2708) and general population (n = 6671) living in Finland who report using health services. Satisfaction with experienced respect for privacy during treatment, benefit of treatment and smoothness of treatment are predicted by region of origin using logistic regression. Almost all foreign-born groups were less likely to consider treatment appointments beneficial as compared to the general population. Some foreign-born groups (people from Southeast Asia and South and Central Asia) were more satisfied with smoothness of care compared to general population. People from East Asia were less likely than the general population to consider that their privacy had been respected during the examinations and treatment. While we made the positive finding of high overall satisfaction with treatment, we also found important differences between groups. In particular, appointments were found less useful among the foreign-born population. Perceived unusefulness of treatment might lead to underuse of health care, which might result in accumulation of untreated health problems. The results point toward potential development points in the health care system. Addressing these issues might help decrease health disparities between population groups.